P‐88: Enhancement of Electro‐Optic Properties of Optically Isotropic Liquid Crystal Device for Flexible Display. Issue 1 (June 2015) - Shin, Eun Jeong; Noh, Seong Cheol; Kim, Tae Hyung; Kim, Jee Hun; Nayek, Prasenjit; Lee, Myong‐Hoon; Kim, Min Su; Chien, Liang‐Chy; Lee, Joun Ho; Kim, Byeong Koo; Lee, Seung Hee
Abstract : Polymer dispersed nano‐sized liquid crystal (LC) composite which is an optically isotropic liquid crystal (OILC) has been investigated looking for its application to flexible liquid crystal displays (LCDs). In the device, nematic LC droplets with its diameter of 242nm are dispersed in polymer matrix so that the LCD has many advantages such as free touch mura, high contrast ratio, rubbing free, wide viewing angle and its phase stability with least hysteresis. However, it needs to overcome high operating voltage and low transmittance. Optimization of LC mixture and controlling ratio of LC and Polymer in the mixture to overcome such barriers are required.